Football Game and Tactical Training - Ionel Caius Drula (Bulletin of the Transilvania University of Braşov: Series IX Sciences of Human Kinetics)
Versatile players are an essential part of modern football, which no longer allows us to talk about attacking or defensive players but rather players with complex talents who can manage any circumstance the game demands. The results of the study demonstrate how important it is for teachers to be involved in helping students learn the best teaching techniques in order for them to become proficient soccer players. To advance game models in the areas of technical procedures and tactical behavior that enhance the activity of those involved in the field and provide them with a good opportunity to analyze a football game, this article need to compare the differences that manifest themselves in the organization of the teams.